2019
DOI: 10.1108/jedt-03-2019-0072
|View full text |Cite
|
Sign up to set email alerts
|

Key risk factors affecting renewable energy independent power producer (IPP) set-up projects in developing countries

Abstract: Purpose Sustained access to efficient electricity plays an essential role in improving living conditions of people and contributes to the economic development of the nation as a whole. Volta River Authority (VRA) mainly manages the generation plants (hydropower sources and thermal plants) alongside independent power producers (IPPs). Power generation in the country has been influenced by myriads of factors. Thus, the purpose of this study is to assess the key risk factors affecting renewable energy of IPPs set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Each stage of the project is characterized not only by a strictly individual set of risks, but also by the level of influence and probability of risks. Studies (Addy et al 2019;Adıyeke et al 2019;Sim and Kim 2019) have shown that the distribution of specific and common risks across the three stages of renewable energy projects is the following:…”
Section: Source: Own Resultsmentioning
confidence: 99%
“…Each stage of the project is characterized not only by a strictly individual set of risks, but also by the level of influence and probability of risks. Studies (Addy et al 2019;Adıyeke et al 2019;Sim and Kim 2019) have shown that the distribution of specific and common risks across the three stages of renewable energy projects is the following:…”
Section: Source: Own Resultsmentioning
confidence: 99%
“…Licensing of regenerable energy projects is cumbersome and costly hence making investors to shy away [3,84] Lack of awareness about the potentials of renewable energy in Ghana hence people do not invest in it [3] Lack of financing for solar consumers [85] High cost of setting up the renewable energy due to high interest rates charged [3,86] Loss of power while it is distributed [3] Poor access to the grid limits the upgrading the network to high quantum of renewable energy [86] Lack of technical skills to operate and maintain the renewable energy systems and technology [86,87] Absence of all-inclusive energy policy has affected the distribution of renewable energy technology in rural areas.…”
Section: Weaknessmentioning
confidence: 99%
“…Climate change awareness hence there is a need of promoting renewable energy to reduce the negative effects to the environment [3] Availability of funds such as Climate Investment Funds (CIF), Sustainable Energy Fund for Africa (SEFA) and the Global Environmental Facility (GEF) these funds are used for financing renewable energy particularly reducing GHGs and develop sustainable energy [3] Increasing electricity demand in industrial, residential, and commercial sectors with an annual growth rate between 10 and 15% per annum hence there is need of increasing the supply of electricity through renewable energy [3] The prices of renewable energy equipment's are reducing hence this is an alternative cheaper method of generating electricity [3] Regional integration of the West African states in form of (ECOWAS) will help to consolidate the region's power generating sources to boost the supply of electrical [3] Threats Subsidizing fossil fuel hinders people from using alternative energy sources of renewable energy [3,86] Changing climatic regions will affect the production of renewable energy that depend on weather [3] Unreliable and inefficient data on renewable energy hence limiting development and large-scale production on renewable energy [3] The current land ownership system (customary, public and vested) in Ghana poses as a huge threat to the development of renewable energy, particularly solar and wind that require large and accessible area of land [3,84] Inconsistency in the policy leads to lack of implementation of previous projects [3] to encourage the expansion of mini-hydro and other mini-grid-connected renewable energy. However, the lack of well-documented tariff principles and a lack of sufficient regulatory capacity for mini-grid systems have consistently operated as roadblocks.…”
Section: Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these methods, the most notable is the integration of the Doublely technique for order of preference by similarity to ideal solution and process failure mode effect analysis [23], the integration of failure modes and effects analysis, and the proactive maintenance strategies [24], and the fuzzy comprehensive evaluation with artificial neural network [25]. Other methods include surveys and risk significance index [26], cross-case analysis [27], GISbased multi-criteria decision analysis [28], and analytical hierarchy process [29]. Research by Albana and Saputra [30] integrated risk management and NPV-at-Risk.…”
Section: Introductionmentioning
confidence: 99%